Should there be biomolecular pragmatics? - Suren T. Zolyan (Слово.ру: балтийский акцент)
This article demonstrates that the concept proposed by Alexander Spirov reflects the ongoing paradigm shift and inspires new approaches in biosemiotics and semiotic pragmatics. The shift involves a move from describing coding languages to describing languages that regulate them. This requires considering the agentivity (or quasi-subjectivity) of sign systems, which leads to a scenario where the sign system functions as both its subject and object, thus reviving Peirce's idea of the sign as a quasi-mind. An analysis of the primary regulatory mechanisms shows that regulatory codes: (a) create specific conditions for coding, (b) govern and control coding processes, and (c) consist of the same elements as coding elements, although are interpreted differently. Their interpretant is not amino acids or proteins but the processes of activation or suppression. Communication and information processes at the biomolecular level allow pragmatics to be understood as semiotic operations associated with intra-system self-regulation and the system's external interaction with its context (environment). The processes within a system, as described by Alexander Spirov, create contexts and interfaces for interaction between different systems. This implies that a system of signs can act as an agent that communicates or interprets, akin to Peirce's notion of the quasi-mind. This understanding has the potential to significantly reshape the current approaches to pragmatics and semiosis.